Sulfato de cobre como estimulante do crescimento de leitões após a dasmama - Vaz de Mello, Hélcio; Alves Torres, Ciro Alexandre; Alves Pereira, José Aldemir; Hemetério D M Carneiro, Luiz; Melgaço A Costa, Paulo (Revista Ceres, 2025)
Sixty growing pigs (36 Duroc-Jersey and 24 crossed Duroc x Wessex-Saddleback) weigthing about 12,24 kg with 60 to 75 days of age were used at the Federal University of Viçosa to study the effect of levels of copper on the performance of the animals, carcass qualities and levels of liver copper for growing finishing pigs.